If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + -1x = 5 + x Solving 7 + -1x = 5 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 7 + -1x + -1x = 5 + x + -1x Combine like terms: -1x + -1x = -2x 7 + -2x = 5 + x + -1x Combine like terms: x + -1x = 0 7 + -2x = 5 + 0 7 + -2x = 5 Add '-7' to each side of the equation. 7 + -7 + -2x = 5 + -7 Combine like terms: 7 + -7 = 0 0 + -2x = 5 + -7 -2x = 5 + -7 Combine like terms: 5 + -7 = -2 -2x = -2 Divide each side by '-2'. x = 1 Simplifying x = 1
| -x+6=-2x+6 | | 2x-7=-x+5 | | f(x)=2*x^3-21*x^2+36*x+1 | | 6+8c=-10 | | -13+4=m-7 | | 8x+24=16x-48 | | -10x+50=-20x-20 | | a^2+19a+18=0 | | -3x+(-8)x+19=16+16 | | -9-n=-4 | | (2)7x-8=64 | | 5x+6=2x-24 | | (19b-9)-9(2b+2)=-5 | | x+12=-5x | | 4m-4=4m+m | | 0.015=0.154x+0.036 | | -4x^2=24 | | f(x)=2x^3-21x^2+36x+1 | | 7(x+9)-6= | | 7-4=9 | | 8x+1=3x+29 | | 17-x=2x-10 | | -2x^2+60=-20 | | -3m=3 | | 5-4x=-53 | | 12=-4(-6+3) | | -n=1 | | p^2+20p=c | | 20c=25n+7 | | -3k-12= | | 37x-21x+8=200 | | 12+y=b |